PENERAPAN LOGARITMA PADA PARAMETER PERMESINAN UNTUK MENENTUKAN KEMUDAHAN PROSES ELECTRICAL DISCHARGE MACHINING - Lestari, Nidia (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2015)
The ease of machining a work piece by Electrical Discharge Machining (EDM) processes is determined by theory. A method in order to obtain the forecast model which can be used as initial prediction that made the EDM process easier by using an approach between the required energy during machining process and λ, θ, and ρ variables has been developed in this research. A methods used for establishing the formula is Logarithm-Algebra Operations. The formula chosen in this investigation is generated by Logarithm-Algebra Operations which has R2 value of 0.7477. This result shows that the percentage of formula effect on value of total energy of discharge pulses (Et) predicted is 74.77%. Material which has the lowest value calculated using formula is the material that is predicted will be the easiest to be machined so that the suitable electrodes could be determined. The suitable electrodes will reduce the energy needed during machining and the tool electrode wear